KONSELING ISLAMI MELALUI TAHLILAN UNTUK MENGATASI KETIDAKDISIPLINAN SHALAT ANAK DI DESA LANDUNGSARI [ISLAMIC COUNSELING THROUGH TAHLILAN TO OVERCOME DISCIPLINE CHILDREN'S PRAYER IN LANDUNGSARI VILLAGE] - Nadhifatuz Zulfa; Nisa'ul Kamilah (Journal of Contemporary Islamic Counselling, 2022)
This paper intends to find out the implementation of the tahlilan tradition as a technique in Islamic counseling to overcome the indiscipline of praying in children in Landungsari village, Pekalongan City. The tahlilan tradition contains a series of activities in which dhikr readings and the Koran are read followed by religious lectures. The controversial tahlilan tradition as a form of heresy, actually contains many positive activities, and has Islamic values. So the bid'ah claim to the tahlilan tradition needs to be reviewed. Among the positive values of this tahlilan tradition is that in addition to the habit of reading dhikr and the holy verses of the Qur'an, it can also be a technique in overcoming indiscipline in praying for children in Landungsari village, especially in RT 03 RW 013 Kec. Pekalongan Timur Pekalongan City. This research is a qualitative descriptive research and a phenomenological approach, with data collection techniques through interviews, observation and documentation. The results of the study proved that the tahlilan tradition was able to overcome indiscipline in praying for children in Landungsari Village, Pekalongan City. Initial conditions and conditions after a month or four times of following tahlilan, based on three indicators of prayer discipline, on the aspect of punctuality experienced a positive change with an increase of 65% from the initial conditions, from the aspect of the accuracy of the terms and pillars of prayer experienced a positive change with an increase of 30% from the initial condition , and from the consistent aspect, there was a positive change with an increase of 75% from the initial condition.